Swimming pool exposure is associated with autonomic changes and increased airway reactivity to a beta-2 agonist in school aged children: A cross-sectional survey - Rufo, JC (2018)
Background Endurance swimming exercises coupled to disinfection by-products exposure has been associated with increased airways dysfunction and neurogenic inflammation in elite swimmers. However, the impact of swimming pool exposure at a recreational level on autonomic activity has never been explored. Therefore, this study aimed to investigate how swimming pool attendance is influencing lung and autonomic function in school-aged children. Methods A total of 858 children enrolled a cross sectional survey. Spirometry and airway reversibility to beta-2 agonist, skin-prick-tests and exhaled nitric oxide measurements were performed. Pupillometry was used to evaluate autonomic nervous function. Children were classified as current swimmers (CS), past swimmers (PS) and non-swimmers (NS), according to the amount of swimming practice. Results Current swimmers group had significantly lower maximum and average pupil constriction velocities when compared to both PS and NS groups (3.8 and 5.1 vs 3.9 and 5.3 vs 4.0 and 5.4 mm/s, p = 0.03 and p = 0.01, respectively). Moreover, affinity to the beta-2 agonist and levels of exhaled nitric oxide were significantly higher in CS when compared to NS (70 vs 60 mL and 12 vs 10 ppb, p< 0.01 and p = 0.03, respectively). A non-significant trend for a higher risk of asthma, atopic eczema and allergic rhinitis was found with more years of swimming practice, particularly in atopic individuals (beta = 1.12, 1.40 and 1.31, respectively). After case-case analysis, it was possible to observe that results were not influenced by the inclusion of individuals with asthma. Conclusions Concluding, swimming pool attendance appears to be associated with autonomic changes and increased baseline airway smooth muscle constriction even in children without asthma.